(untitled) (Botanica Orientalis: Journal of Plant Science, 2019)
One of the most common impacts of air pollution on plant species is the gradual loss of chlorophyll and concomitant yellowing of leaves, which results in decrease in the capacity of photosynthesis. In the present study, effect of air pollutants on chlorophyll content of some selected plant species along the roadsides of Kathmandu Valley was assessed. Five commonly occurring plant species along the roadside, viz. Bougainvillea glabra, Duranta erecta, Lantana camara, Ricinus communis and Sambucus chinensis were selected for the study. The study revealed lowest concentration of chlorophyll “a”, chlorophyll “b” and total chlorophyll in the leaf samples of all species collected from heavily polluted site (Thamel) when compared with the leaf samples collected from the control site (Tribhuvan University Area, Kirtipur). Chlorophyll content was insignificantly reduced in Bougainvillea glabra in heavily polluted site, but a significant reduction was recorded in Sambucus chinensis. Maximum reduction in chlorophyll content exhibited by Sambucus chinensis can be ascribed to sensitiveness of the species to air pollution, while least reduction in chlorophyll content by Bougainvillea glabra suggests that it is an air pollution tolerant species. This study clearly indicated that the vehicular air pollution affected the level of chlorophyll pigments in plants exposed to roadside.